Research progress on high entropy oxide ceramics: Principles, preparation, and properties - Gang Du; Canhua Li; Jiamao Li; Guangchao Wu; Zhenyi Huang; Aiqin Mao; Mengchen Ma; Zhiyun Guo; Zhao Chen (Journal of Materials Research and Technology)
High entropy oxide ceramics impart diverse excellent characteristics and extensive application potential to the high entropy oxide family, owing to their distinct high entropy effects and lattice distortions. Starting from the basic definition of entropy, this article provided a detailed introduction to the design principles of high entropy oxide ceramics. It summarizes five main crystal types: rock salt type, fluorite type, perovskite type, spinel type, and pyrochlore type. The three main preparation processes of solid-phase method, liquid-phase method, and gas-phase method are summarized, and the performance and applications of high entropy oxide ceramics in the fields of thermodynamics, mechanics, catalysis, and electromagnetic energy storage are deeply explored. Finally, this article provides an outlook on the development direction and future trends of high entropy oxide ceramics, providing inspiration and reference for further research in this field.